PERBEDAAN KEMAMPUAN BERCERITA ANAK USIA DINI 5-6 TAHUN MELALUI PENGGUNAAN MEDIA BONEKA JARI DI TK SALSA DESA CINTA RAKYAT - Sophi Juniandari; Isa Hidayati (ADIBA : JOURNAL OF EDUCATION, 2025)
This study aims to identify differences in storytelling ability in early childhood aged 5-6 years through the application of finger puppet media in Salsa Kindergarten, Cinta Rakyat Village. The method used is a quantitative approach with a Quasi Experimental Design, specifically the Pretest-Posttest Control Group Design, which is used to compare two groups. The population in this study was 40 children aged 5-6 years. The sample was selected randomly (random sampling), consisting of 20 children in class B1 (Sun Class) as the experimental group who received treatment, and 20 children in class B2 (Star Class) as the control group without treatment. Data were collected through observation, testing, and documentation systematically. Data analysis was carried out using descriptive analysis and non-parametric statistics through the Mann-Whitney U test. The results showed that there was a significant difference in storytelling ability between children who used finger puppet media and those who did not. This is indicated by the significance value of the Mann-Whitney U test of 0.026 <0.05. Thus, finger puppet media has proven effective in improving the storytelling skills of early childhood children at Salsa Kindergarten, Cinta Rakyat Village.